Female Labor Supply and Child Care in France - Philippe Choné; David le Blanc; Isabelle Robert-Bobée (Center for Economic Studies and ifo Institute (CESifo), 2003)
We use French household data to estimate a structural model of female labor supply and use of paid child care outside the home. Child care costs are found to have little impact on the labor market participation decision of mothers. The model is used to study various policy issues. The influence of the current tax credit on child care expenditures on the mothers' labor supply is weak. Suppressing the APE (Parental Allowance for the Education) would cause the female participation rate in our sample to rise by 4 points and the proportion of mothers using paid care to rise by 2 points. The responses of women to policy changes are very heterogenous. Macroeconomic changes in female labor supply are equally due to switches between non-participation and participation and switches between working hours by working women.
Keywords: 330; female labor supply; child care; welfare participation; fiscal policy